« Un feu brûle en moi » : dernières lignes du « Kaddish final » d’André Schwarz-Bart - Keren Mock (Continents manuscrits)
Whereas there are many academic publications on André Schwarz-Bart, one of his works that could be considered as major, “Kaddish”, remains still to be discovered. Cut-out and annotated newspapers and magazines, notebooks, and a library full of books with marginalia: such seems to be the form of this archive with important dimensions. By a comparative search for the scattered traces of this prayer to be invented, this article deals with the analysis and the processes of an experimental kind of writing. Through the two versions found in André Schwarz-Bart’s archives of the ancient lamentation “A Fire Burns Whithin Me”, the project is to reconstruct a considerable work left in its nascent state. Written directly on Yosef Hayim Yerushalmi’s Zakhor or rewritten in the form of a play, Schwarz-Bart’s writing adds to the ritual and liturgical imperative to remember of the Jewish people, the traumatic memory of the Holocaust.